Effects of Soret diffusion on spherical flame initiation and propagation. (March 2015) - Han, Wang; Chen, Zheng
Abstract: Dynamics of spherical flame initiation and propagation with Soret diffusion are investigated using large-activation-energy asymptotic analysis. Under the assumptions of constant density and quasi-steady flame propagation, a general correlation between the flame propagating speed and flame radius considering Soret diffusion and external energy deposition is derived. Emphasis is placed on assessing the effects of Soret diffusion on spherical flame propagation speed, Markstein length, and critical ignition condition. The stretched flame speed is found to be increased and reduced by the Soret diffusion of light and heavy fuels, respectively. For both light and heavy fuels, the absolute value of Markstein length increases after including Soret diffusion, indicating that premixed flames become more sensitive to stretch rate with Soret diffusion. It is found that the Markstein length can be characterized by an effective Lewis number which includes the effects of Soret diffusion. Moreover, Soret diffusion is shown to affect the ignition process since the spherical flame kernel is highly stretched. For large hydrocarbon fuels with high Lewis numbers, the minimum ignition power becomes much larger after considering Soret diffusion.